Navigating the Unprecedented: Leading Remotely Unexpectedly - Matthew Sowcik; Megan Stein (EDIS)
Leaders tend to have a set of assumptions or ideas about how to do their job. As the world moves quickly to social distancing and remote work, leaders rely on their assumptions to navigate this new landscape. Different frames of reference can act as a road map allowing leaders to take the first steps into the unknown. This new 4-page article utilizes these Bolman and Deal's four frames addressing different aspects of leadership to provide best practices for leading in a remote work environment. Written by Matthew Sowcik and Megan Stein, and published by the UF/IFAS Department of Agricultural Education and Communication. https://edis.ifas.ufl.edu/wc354